IMPLEMENTASI PENDIDIKAN ANTI KORUPSI MELALUI HABITUASI DAN PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN UNTUK MEMBANGUN KARAKTER SISWA DI SMP NEGERI 1 CIANJUR - Apiek Gandamana (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2018)
This study generally aims to describe and analyzing in depth the implementation of anti-corruption education and learning through habituation Civics. Research process using a qualitative approach with descriptive methods. Results showed that the implementation of anti-corruption education is done by integrating anti-corruption education material into Civics subject because when used as a separate subject would burden the students itself, the habituation performed by all people in schools environment that instill the values of honesty, and discipline, as well as a canteen of honesty as a form of students habituation to do what is rightKeywords: Anti-Corruption Education, Habituation, Character.